Biosorption of chromium (VI) from aqueous solution by dried water hyacinth (Eichhornia crassipes) - Mohd Zamri, Zainuddin (2009)
Metal ions in wastewater can cause serious toxicological problem which are dangerous to the environment and human being. Hexavalent chromium Cr (VI) is very toxic and mutagenic for most organisms. It is essential to remove this metal from wastewater. The purpose of this study is to investigate the performance of dried water hyacinth (Eichhornia crassipes) in biosorption of hexavalent chromium, Cr (VI). The effect of biosorbent dosage, initial concentreation, initial pH of the solution, and time contact were studied and the optimum conditions for biosorption process were indentified. Only the stems and leaves of the water hyacinth were use as the biosmass in this study. Biomass is mixed with the chromium solution at specific condition before the supernatant is taken. Supernatant were analyzed using atomic absorption spectrophotometer (AAS) in order to determine the concentration of chromium in the solution. Results show that biosorption of chromium (VI) highly depends on parameter studied. The amount of chromium adsorbed depends on the dosage. High loading of biomass will increase the removal of chromium. Low initial concentration also will make sorption yield higher. Biosorption of chromium (VI) is greatly depending on pH value because at pH more than, 2 the amounts of chromium remove is lower. When the time contact between biosorbent and solution increase, the removal of chromium also increase. The optimum condition for biosorption of chromium were at 0.7g biosorbent loading, initial concentration at 5mg/L, 1.8 pH value and 75 minutes of time contact.